Treatment of aquaculture effluent with floating macrophytes: systemic review and meta-analysis (Research, Society and Development, 2022)
Aquaculture is the production of organisms that present partial or total development in water, generating an effluent rich in nutrients. The use of artificial foods is common in production, but they are highly nutritious in nitrogen and phosphorus. Such nutrients are sources of energy for aquatic plants, such as macrophytes. The use of macrophytes for nutrient absorption is common in some treatment systems such as wetlands. The objective was to carry out a systemic review and meta-analysis of the efficiency of the use of floating macrophytes for the treatment of aquaculture effluent. The platforms used were Capes Journals, Scopus and Web of Science. From the articles found, data were collected from authors, year of publication, published scientific journal, macrophyte species, characteristics evaluated in the effluent and place of study. Means and standard deviations were used for statistical analysis, through the standardized mean difference (SMD), method for performing the meta-analysis. Only 24 articles were included in the systemic review, but only 9 articles were able to extract the necessary information to carry out the meta-analysis. Among the chemical properties, pH was the most measured, being present in 21 articles. The most common macrophyte genera were Eichhornia, Pistia, Lemna, Salvinia and Azolla. Only the meta-analysis of orthophosphate showed no statistical difference, while total nitrogen, ammonia, nitrite, nitrate, total Kjeldahl nitrogen, total inorganic nitrogen, total phosphorus and orthophosphate were significant. It can be seen that macrophytes have a greater affinity for certain nutrients.